Evaluating the generic definition of Lithopolia Yoshimoto, 1993 with a description of one new species of Taiwan (Lepidoptera, Noctuidae, Noctuinae, Orthosiini) - Wu, Shipher; Yen, Shen-Horn (Zootaxa, 2019)
The present study evaluates the relationships among the Orthosiini genus Lithopolia Yoshimoto, 1993 and its related genera in Egira Duponchel, 1845 group. We propose the absence of signum on corpus bursae can be regarded as the synapomorphic character of Lithopolia. Based on this character, we transfer Egira phahompoki Hreblay & Ronkay, 1999 of N. Thailand (type locality) and W. China (new record) to Lithopolia (comb. nov.) and describe a closely related new species, L. tadaokanoi sp. nov., from Taiwan. The inner relationship of Lithopolia is also discussed.